The Meaning of the Ngaben Ceremony Tradition in the Process of Accepting Grief: An Indigenous Psychology Approach in Bali - Grefanti, Risa; Hastangka, Hastangka (Jurnal Impresi Indonesia, 2025)
This reflective paper addresses how the Balinese community interprets and performs the Ngaben ceremony as part of the grieving and acceptance process following the loss of a loved one. The main idea of this paper is that cultural rituals such as Ngaben play a significant psychological role in helping individuals and families cope with sorrow. The author was inspired to explore this theme upon observing that Ngaben is not merely an obligatory tradition, but also serves as a form of collective healing that remains relevant today. The purpose of this paper is to describe and explore the meaning of the Ngaben ritual within the framework of Indigenous Psychology. The writing method used is reflective and contextual, referring to the cultural context and spiritual meaning held by the Balinese people. This paper aims to provide a deeper understanding of how local culture functions as a psychological mechanism in the grieving process, and to contribute insight into the importance of culturally-based approaches in psychological studies.